Speech Acts and Relevance: in Search of a Dialogue - Iwona Witczak-Plisiecka (Research in Language)
This paper comments on the notion of the speech act in the tradition of J.L. Austin (1962/1975) in an attempt to assess its relevance (sic!) in a relevance-theory-based research. Relevance theory (RT) since its introduction (Sperber & Wilson 1986/1995) has consistently rejected much of speech act-theoretic thinking, explicitly questioning its having a central position in pragmatics. Using the notion of “the speech act”, RT seems to ignore most of speech act-theoretic apparatus. However, despite the superficial divergence between the two frameworks, the advancements within RT, as developed especially by Deirdre Wilson, and her co-researchers over the years, are convergent with selected thoughts in the Austinian thought. The paper comments on selected points which bring the two linguistics approaches together.